Analysis Of Riba (Usury) From A Religious Understanding Perspective Among The Community In Sungai Rantai - anisa marseli; rinaldi rinaldi (Al-Hijrah: Journal of Islamic Economics And Banking, 2023)
This article describes the problem of usury law from the perspective of public understanding. As for some of the Sungai Rantai people who consider usury to be a common practice that they have done since long ago from their ancestors, the Sungai Chain community considers usury to be a source of their livelihood because the profit they get is many times that of them. seek honest income or lawful livelihoods, therefore the Sungai Rantai community often commits acts of usury. It is said that usury is one of the major sins in Islam, because it leads to destruction. Therefore, providing understanding to the public actually aims to advance an economic system that is compassionate, more just, more balanced social relations and ethical values that are in line with Islamic teachings